Prevalence and risk factors for overweight horses at premises in Sweden assessed using official animal welfare control data. Issue 1 (October 2016) - Hitchens, Peta; Hultgren, Jan; Frössling, Jenny; Emanuelson, Ulf; Keeling, Linda
Abstract Background There are Swedish animal welfare regulations concerning the body condition of horses and general advice on keeping horses including that horses should be fed so that they do not become over- or underweight relative to their use. Compliance is assessed by official animal welfare inspectors. The objective of this study was to determine whether the national animal welfare control database could be used to estimate the prevalence and risk factors for overweight horses in Sweden. The official animal welfare control checklist for horses contains 45 checkpoints (CP) of which CP-8 pertains to the acceptability of the horses' body condition including whether they were under- or overweight. Prevalence of non-compliance with CP-8, with 95 % confidence intervals (CI), were calculated for the years 2010–2013. Associations between risk factors and non-compliance for overweight body condition were estimated using logistic regression and expressed as odds ratios (OR) with 95 % CIs. Results Of 7870 premises with registered horses that were inspected against CP-8, a total of 63 premises had non-compliant inspections due to overweight horses (0.80 %; CI 0.62, 1.02 %). In multivariable analyses, premises that were non-compliant with requirements for the care of sick or injured horses (OR 3.52; CI 1.51, 8.22) or with the requirements for feeding a balanced high-quality diet (OR 5.15; CI 2.49, 10.67) had greater odds of having overweight horses. Premises that also kept other species for meat production were more likely to have overweight horses (OR 2.12; CI 1.18, 3.81) whereas professional horse establishments were less likely (OR 0.09; 0.01, 0.64). Overweight horses were more likely in summer compared to winter (OR 2.18; CI 1.02, 4.70). Premises in regions of Sweden with more horses in relation to the human population were less likely to have overweight horses (OR 0.97; CI 0.95, 1.00). Conclusions Official animal welfare control data may be used to monitor the premises prevalence of overweight horses in Sweden. Strategies to reduce the prevalence of overweight horses should focus on education about equine care and nutrition, especially summer grazing.